Discursive Heterogeneity in The Autobiography of Miss Jane Pittman by Ernest J. Gaines - Tia, Daniel (International Journal of Culture and History, 2024)
Various critics are interested in the aesthetic scope of literary discourse; those who are truly inscribed in that perspective, adopt varied approaches. Accordingly, countless meanings are given to the same literary texts. What is termed “discursive heterogeneity” in the current study is purely ideological and is about the implicit views entertained by colonists during and after colonial period, which are symbolically romanticized by African American writers as illustrated by Ernest J. Gaines in The Autobiography of Miss Jane Pittman (Note 1). That novel is a symbolic instance in which a double period, marked by distinctive ideological discourses, intertwine in a unified and dynamic way, thus creating a narrative harmony. The former differs from the latter by its unilateral characteristics, which imposes an exclusive submission upon Blacks and the latter is opposed to the former by its controversial ambivalence, granting restricted liberties to Blacks. Practically, Blacks are free without actually being free. A close glance at the type of communication prevailing between white colonists and black folks before the Proclamation of Freedom helps to discover its unilateralism (downward communication) and the post-Proclamation one is bi-dimensional (downward and upward communication). But between both preceding periods, there is the Proclamation of Freedom, whose message is more constraining and transcendental in the narrative universe. So, to learn more about that “discursive heterogeneity” and bring out its related meanings, this study leans on narrative semiotics. That methodological tool examines the discursive clues; particular attention is paid to Blacks’ evolution from the period before the Proclamation of Freedom up to the prevailing era after the Emancipation.